Failure of salmeterol to inhibit circulating white cell responses and bronchoconstriction induced by platelet activating factor. Issue 11 (November 1992) - Spring, J; Johnston, S R; Seale, J; Ind, P W
Abstract : BACKGROUND: Platelet activating factor (PAF) is a potent mediator of inflammation. Inhalation of PAF causes acute bronchoconstriction and a transient fall in white blood cell count in humans. Salmeterol inhibits pulmonary inflammation induced by PAF in guinea pigs. METHODS: The effect of salmeterol on effects induced by PAF was investigated in eight normal subjects who inhaled salmeterol (50 micrograms) twice daily or a matched placebo for one week before challenge with PAF. Blood samples were taken from a forearm catheter for total white cell and neutrophil counts before and for 30 minutes after administration of PAF (48 micrograms) through a Mefar dosimeter. Blood films were stained for unsegmented neutrophils before and after treatment with PAF on a placebo day. RESULTS: Mean baseline total white cell counts and neutrophil counts did not differ on the two days. Mean baseline sGaw was significantly higher after inhaled salmeterol (1.84 (95% C1 1.45-2.23) s-1kPa-1) than after placebo (1.53 (1.24-1.82)). After placebo mean total white cell counts, neutrophil counts, and sGaw were reduced to 60 (43-78)%, 39 (14-64)%, and 82 (71-93)% of baseline respectively five minutes after inhaled PAF. After salmeterol treatment mean reductions five minutes after inhaled PAF were 59 (45-73)%, 40 (19-61)%, and 82 (71-93)% of baseline respectively. At 30 minutes after treatment with PAF the neutrophil count rebounded to 143 (82-204)% of baseline after placebo and to 127 (93-161)% after inhaled salmeterol. There was no significant difference in the percentage of immature neutrophils before and after treatment with PAF (2.0 (0.5-2.6)% compared with 3.9 (2.2-5.6)%. CONCLUSIONS: Treatment with salmeterol did not inhibit reduction in total white cell count or neutrophil count, rebound neutrophilia, acute bronchoconstriction, or transient flushing after inhalation of PAF. These results conflict with the inhibitory effect of salmeterol on lung inflammation in guinea pigs but are consistent with the lack of effect of salbutamol in humans. Salmeterol does not have an anti-PAF effect in vivo in humans.